2012
DOI: 10.1074/jbc.m112.418640
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic GH Loop Regulates the Phosphatidylinositol 4,5-Bisphosphate-induced Gating Kinetics of Kir2 Channels

Abstract: Background:The detailed mechanism of PIP 2 -induced Kir channel gating remains elusive. Results: Specific mutations increase the flexibility of the cytosolic GH loop and accelerate the PIP 2 -induced gating kinetics of Kir2 channels. Conclusion: Interactions of the GH loop with the N terminus regulate the PIP 2 -induced gating kinetics of Kir2 channels. Significance: We identify a novel region in Kir channels involved in the control of PIP 2 -induced gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…36 Specifically, it has been shown that mutation of E272, which is located between N251 and Y280/ L282, affects both the on-and off-gating kinetics of the channel. Moreover, we have recently shown that in addition to reversing the effect of the L222I mutation on the sensitivity of Kir2.1 to cholesterol, N251D also restores the strength of the interaction of the L222I mutant with PI(4,5)P 2 to the levels exhibited by the WT Kir2.1 channel.…”
Section: Discussionmentioning
confidence: 99%
“…36 Specifically, it has been shown that mutation of E272, which is located between N251 and Y280/ L282, affects both the on-and off-gating kinetics of the channel. Moreover, we have recently shown that in addition to reversing the effect of the L222I mutation on the sensitivity of Kir2.1 to cholesterol, N251D also restores the strength of the interaction of the L222I mutant with PI(4,5)P 2 to the levels exhibited by the WT Kir2.1 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Such rearrangements may also promote disengagement of the CTD from the TM/ pore domain, thereby allowing it to move down/away and into the closed state conformation. Interestingly, many previous studies have also suggested that the flexibility and movement of the G-loop is critical for gating in several different Kir channels 11,12 and may even act as a physical gate 13 (i.e. barrier to ion permeation).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the oocytes were held at −80 mV for the deactivation of Ci-VSP. Sweeps were applied until the resulting currents reached a steady state [22]. A low-potassium solution (ND96) containing 96 mM NaCl, 1 mM KCl, 1.8 mM CaCl 2 , 1 mM MgCl 2 , and 5 mM HEPES (pH 7.4 with NaOH) was used to inhibit most of the Kir currents at −80 mV.…”
Section: Methodsmentioning
confidence: 99%
“…Two bath solutions were used: an FVP solution containing 60 mM KCl, 5 mM EDTA-K, 5 mM KF, 0.1 mM Na 3 VO 4 , 10 mM K 4 P 2 O 7 , and 10 mM HEPES (pH 7.4 with KOH) and another FVP solution with diC 8 PIP 2 at 0–100 μM for dose-response measurements and at 30 μM for gating kinetics measurements. diC8 PIP 2 was purchased from Avanti Lipids and prepared as described previously [22]. All other chemicals were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation